Neonatal cholestasis as the onset symptom of McCune–Albright syndrome: case reports and a literature review - Fang, Weiyuan; Zhang, Yanhui; Chen, Lian; Xie, Xinbao (Frontiers in Pediatrics, 2023)
Aim This study aimed to summarize and show the characteristics and evolutionary process of neonatal cholestasis caused by McCune–Albright syndrome (MAS), as neonatal cholestasis may be the initial manifestation of MAS before other classic clinical features appear. Methods The clinical characteristics, treatment methods, and outcomes of three neonatal cholestasis cases caused by MAS in our center were retrospectively studied. In addition, all the reported cases of MAS combined with cholestasis were reviewed and summarized to show the cholestatic features in them. Results We have confirmed three MAS cases in our center, presenting onset symptoms of jaundice, pale stool, and neonatal cholestasis soon after birth. The cholestasis subsided spontaneously at around the sixth month. The literature review showed that the levels of total bilirubin, conjugated bilirubin, ALT, AST, and GGT in neonatal MAS cholestasis cases were 207 μmol/L (range 65–445 μmol/L), 162 μmol/L (range 46–412 μmol/L), 821 U/L (range 85–3,597 U/L), 532 U/L (range 127–3,633 U/L), and 244 U/L (range 79–3,800 U/L), respectively. Liver histology showed canalicular and hepatocellular cholestasis, giant hepatic cell transformation, and bile paucity. Extrahepatic manifestations such as café-au-lait pigmented skin lesions, Cushing's syndrome, hyperthyroidism, renal tubular dysfunction, and skeletal abnormalities could occur simultaneously when jaundice occurred. GNAS mutations had a high positive rate (83.3%–100%) in liver tissue with cholestasis. Neonatal cholestasis caused by MAS could be self-resolved, but hepatic lesions persist and have malignant potential. Conclusion MAS can be one of the causes of neonatal cholestasis, which may be the first manifestation of the disease. Extrahepatic coexisting symptoms of MAS and liver histology can help to distinguish MAS from other etiology of cholestasis. Detecting GNAS mutations in liver tissue may shorten diagnostic time and is of particular interest in the partial and atypical forms of MAS with neonatal cholestasis. Neonatal cholestasis in children with MAS can self-resolve, but liver dysfunction and malignant lesions persist.